Zinc oxide nanoparticle-based seed priming enhances germination, growth, and yield in okra (Abelmoschus esculentus L.) - Deepa Pandey; Widhi Dubey (Vegetos, 2026)

Dual effects of ultraviolet radiation (UVR; 280–400 nm) on photosynthesis and stress response in cyanobacterium Synechococcus elongatus PCC 7942 - Deepa Pandey; Sapna Tiwari; Anjali Gupta; Priyul Pandey; Shailendra Pratap Singh (Physiology and Molecular Biology of Plants, 2026)

Occurrence, Characterization, and Potential Ecological Risks of Microplastics in the Himalayan Riverine Systems - Deepa Kumari; Ramendra Pati Pandey; Ankur Rajpal; H. C. Sudheeksha; Smriti Arora (Bulletin of Environmental Contamination and Toxicology, 2026)

Wings across the gradient: butterfly diversity declines along an urbanization gradient in the subtropical Himalayas - Prakash Chandra Aryal; Chandramani Aryal; Dipak Khadka; Abinash Aryal; Kiran Rayamajhi; Sonam Shrestha; Bhaiya Khanal; Deepa Karki; Hari Prasad Pandey; Tek Maraseni (Urban Ecosystems, 2026)

Genetic Variability in Jackfruit (Artocarpus heterophyllus Lam.) for Floral Traits and Fruit Quality Attributes in Eastern Tropical Region of India - Kundan Kishore; Deepa Samant; V. Pandey (Applied Fruit Science, 2025)

A time and temperature dependent biosynthesis of silver nanoparticles using the extract of Platycladus orientalis’ fruit - Deepa; Madhur Babu Singh; Gauri Thakur; Anirudh Pratap Singh Raman; Prashant Singh; Pradeep Kumar; Ravinder Singh; Garima Pandey; Kamlesh Kumari (Next Research, 2024)

Diurnal oscillation in dissolved oxygen at sediment-water interface fuels denitrification-driven N removal in Ganga River - Deepa Jaiswal; Neha Naaz; Shivam Gupta; Ketan Madhav; Jitendra Pandey (Journal of Hydrology, 2023)

Integrating resilience with functional ecosystem measures: A novel paradigm for management decisions under multiple‐stressor interplay in freshwater ecosystems - Deepa Jaiswal; Usha Pandey; Vibha Mishra; Jitendra Pandey (Global Change Biology, 2021)
Moving beyond monitoring the state of water quality to understanding how the sensitive ecosystems “respond” to complex interplay of climatic and anthropogenic perturbations, and eventually the mechanisms that underpin alterations leading to transitional shifts is crucial for managing freshwater resources. The multiple disturbance dynamics—a single disturbance as opposed to multiple disturbances for recovery and other atrocities—alter aquatic ecosystem in multiple ways, yet the global models lack representation of key processes and feedbacks, impeding potential management decisions. Here, the procedure we have embarked for what is known about the biogeochemical and ecological functions in freshwaters in context of ecosystem resilience, feedbacks, stressors synergies, and compensatory dynamics, is highly relevant for process‐based ecosystem models and for developing a novel paradigm toward potential management decisions. This review advocates the need for a more aggressive approach with improved understanding of changes in key ecosystem processes and mechanistic links thereof, regulating resilience and compensatory dynamics concordant with climate and anthropogenic perturbations across a wide range of spatio‐temporal scales. This has relevance contexting climate change and anthropogenic pressures for developing proactive and adaptive management strategies for safeguarding freshwater resources and services they provide.

Bioplastic production from renewable lignocellulosic feedstocks: a review - R. Reshmy; Deepa Thomas; Eapen Philip; Sherely A. Paul; Aravind Madhavan; Raveendran Sindhu; Ranjna Sirohi; Sunita Varjani; Arivalagan Pugazhendhi; Ashok Pandey; Parameswaran Binod (Reviews in Environmental Science and Bio/Technology, 2021)

Anacardic acid encapsulated solid lipid nanoparticles for Staphylococcus aureus biofilm therapy: chitosan and DNase coating improves antimicrobial activity - Md Meraj Anjum; Krishna Kumar Patel; Deepa Dehari; Nidhi Pandey; Ragini Tilak; Ashish Kumar Agrawal; Sanjay Singh (Drug Delivery and Translational Research, 2021)

Potential of native cold tolerant plant growth promoting bacilli to enhance nutrient use efficiency and yield of Amaranthus hypochondriacus - Chitra Pandey; Yogesh Kumar Negi; D. K. Maheshwari; Deepa Rawat; Deepti Prabha (Plant and Soil, 2018)

Oxidative Stress and Genotoxicity of Zinc Oxide Nanoparticles to Pseudomonas Species, Human Promyelocytic Leukemic (HL-60), and Blood Cells - Deepika Soni; Deepa Gandhi; Prashant Tarale; Amit Bafana; R.A. Pandey; Saravanadevi Sivanesan (Biological Trace Element Research, 2017)

Microbial population shift caused by sulfamethoxazole in engineered-Soil Aquifer Treatment (e-SAT) system - Ashwinkumar P. Rudrashetti; Niti B. Jadeja; Deepa Gandhi; Asha A. Juwarkar; Abhinav Sharma; Atya Kapley; R. A. Pandey (World Journal of Microbiology and Biotechnology, 2017)

Characterisation of respirable dust exposure of different category of workers in Jharia Coalfields - Jai Krishna Pandey; Deepa Agarwal; Sanjoy Gorain; Rajnish Kumar Dubey; Manoj Kumar Vishwakarma; Kamlesh Kumar Mishra; Asim Kumar Pal (Arabian Journal of Geosciences, 2017)

Terpenoid composition and antifungal activity of three commercially important essential oils against Aspergillus flavus and Aspergillus niger - Deepa Bisht; Anirban Pal; C.S. Chanotiya; Dhirendra Mishra; K.N. Pandey (Natural Product Research, 2011)

Growth enhancement of black pepper (Piper nigrum) by a newly isolated Bacillus tequilensis NII-0943 - Syed G. Dastager; C. K. Deepa; Ashok Pandey (Biologia, 2011)

Paracoccus niistensis sp. nov., isolated from forest soil, India - Syed G. Dastager; C. K. Deepa; Wen-Jun Li; Shu-Kun Tang; Ashok Pandey (Antonie van Leeuwenhoek, 2011)

Potential plant growth-promoting activity of Serratia nematodiphila NII-0928 on black pepper (Piper nigrum L.) - Syed G. Dastager; C. K. Deepa; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2011)

Plant growth-promoting activity in newly isolated Bacillus thioparus (NII-0902) from Western ghat forest, India - C. K. Deepa; Syed G. Dastager; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2010)

A Web GIS Application for Dams and Drought in India - Devendra Singh Rathore; Deepa Chalisgaonkar; R. P. Pandey; Tanvear Ahmad; Yatveer Singh (Journal of the Indian Society of Remote Sensing, 2010)

Isolation and characterization of plant growth promoting bacteria from non-rhizospheric soil and their effect on cowpea (Vigna unguiculata (L.) Walp.) seedling growth - C. K. Deepa; Syed G. Dastager; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2010)

Characterization of plant growth-promoting rhizobacterium Exiguobacterium NII-0906 for its growth promotion of cowpea (Vigna unguiculata) - Syed G. Dastager; Deepa C. Kumaran; Ashok Pandey (Biologia, 2010)